Short-chain alcohols inactivate an immobilized industrial lipase through two different mechanisms - Mangiagalli, Marco; Ami, Diletta; de Divitiis, Marcella; Brocca, Stefania; Catelani, Tiziano; Natalello, Antonino; Lotti, Marina (Biotechnology Journal, 2022)
Broadly used in biocatalysis as acyl acceptors or (co)-solvents, short-chain alcohols often cause irreversible loss of enzyme activity. Understanding the mechanisms of inactivation is a necessary step toward the optimization of biocatalytic reactions and the design of enzyme-based sustainable processes. The functional and structural responses of an immobilized enzyme, Novozym 435 (N-435), exposed to methanol, ethanol, and tert-butanol, are explored in this work. N-435 consists of Candida antarctica lipase B (CALB) adsorbed on polymethacrylate beads and finds application in a variety of processes involving the presence of short-chain alcohols. The nature of the N-435 material required the development of an ad hoc method of structural analysis, based on Fourier transform infrared microspectroscopy, which was complemented by catalytic activity assays and by morphological observation by transmission electron microscopy. The inactivation of N-435 was found to be highly dependent on alcohol concentration and occurs through two different mechanisms. Short-chain alcohols induce conformational changes leading to CALB aggregation, which is only partially prevented by immobilization. Moreover, alcohol modifies the texture of the solid support promoting the enzyme release. Overall, knowledge of the molecular mechanisms underlying N-435 inactivation induced by short-chain alcohols promises to overcome the limitations that usually occur during industrial processes.